KERJA SAMA UN WOMEN DENGAN GOJEK DALAM MENDUKUNG AGENDA SUSTAINABLE DEVELOPMENT GOALS-5: GENDER EQUALITY DI INDONESIA - Indah Jullanar; M. Chairil Akbar Setiawan; Wiwiek Rukmi Dwi Astuti (Indonesian Association for International Relations, 2024)
This article aims to describe the collaboration between UN Women and Gojek which was agreed in July 2020 in pushing for the achievement encouraging the SDGs-5: Gender Equality in Indonesia. The theory used is gender equality in the perspective of feminism, feminist institutionalism theory, and sustainable development in the type of qualitative research. Data collection was taken through internet-based research and data analysis techniques using interactive data analysis models. The results of the research show that the cooperation by UN Women and Gojek is divided into three framework areas of work namely increasing women's capacity, strengthening the capacity of MSMEs, and promoting women's safety in public spaces. The collaboration between UN Women and Gojek is shown as one of the parties involved in helping achieve the SDGs 5 agenda. This is also evidenced by data from the WEF report on the 2022 Global Gender Gap, where the gender equality index in Indonesia has increased from last year